The mediating role of mood in the relationship between perseverative cognition, sleep and subjective health complaints in music students. Issue 6 (3rd June 2019) - Studer, Regina K.; Nielsen, Carole; Klumb, Petra L.; Hildebrandt, Horst; Nater, Urs M.; Wild, Pascal; Heinzer, Raphaël; Haba-Rubio, José; Danuser, Brigitta; Gomez, Patrick
Abstract: Objective : Subjective health complaints (SHC) are frequent in musicians. These complaints may be particularly distressing in this population because they are performance relevant. This paper aims at testing a model positing that (a) perseverative cognition (PC) predicts sleep duration/quality, (b) sleep duration/quality predicts SHC and (c) mood is a mediator of these associations. Design : Participants were 72 music students (mean age (SD): 22.7 (3.0) years), and the assessment period consisted of seven consecutive days, with a solo performance on the fifth day. Main outcome measures : Self-reported total sleep time (TST) and sleep quality were assessed 30 min after wake-up, and objective TST/sleep quality were assessed with an actigraphy watch. PC and mood were measured five times a day. Daily SHC were assessed at 9 p.m. Results : PC did not significantly predict sleep duration/quality. Self-reported and objective TST and sleep quality were all significantly associated with SHC. Mood played a mediating role in each of these relationships with the exception of objective sleep quality. Conclusion : The tested model on the association among PC, sleep and SHC and the mediating role of mood received partial support, highlighting the importance of sleep and mood in the emergence of SHC among university music students.